Development of Crispy Tempeh Chip Products - Sukkaseam, Nattakarn; Buarod, Raweewan; Boonsit, Siriporn; Ochaikul, Duangjai; Sitthitrai, Kamonporn; Saikaew, Kawinchaya (Journal of Food Technology, Siam University, 2025)
This study aimed to evaluate the effect of the tempeh to flour ratio in developing crispy tempeh chip products, using three different ratios: 60:40, 70:30, and 80:20. There are two groups of tempeh: the soybean tempeh group (formulations 1-3) and the mixed legume tempeh group, which includes four different types of legume tempeh: soybean, mung bean, red bean, and tiger-striped peanut (formulations 4-6). We found that formulation 6 (mix-legume tempeh-to-flour ratio, 80:20) was ambitious in forming a thin sheet before baking. The product of formulations 1-5 exhibited the yellow-brown color with the lightness (L*) value ranking between 45.20 and 57.39 and the yellowness (b*) value ranking between 27.55 and 32.80. The high tempeh portion caused an increase in the moisture, protein, and fat contents (p≤0.05) but reduced ash (mineral) and carbohydrate contents (p≤0.05). In addition, the high portion of tempeh led to increases in phenolic, protein, peptide, and antioxidant activity (p≤0.05). Formulation 3 (soybean tempeh-to-flour ratio, 80:20) contained the highest level of total phenolic and total flavonoid of 4.29 mg GAE/g DW and 10.37 mg QE/g DW, respectively. Formulation 2 (soybean tempeh-to-flour ratio, 70:30) contained the highest total peptide content at 156.64 mg BSA/g DW (p≤0.05). However, formulation 1 (soybean tempeh-to-flour ratio, 60:40) provided the highest hedonic scores of all attributes, ranked between like moderately and like very much. Meanwhile, the overall liking score of formulation 1 was similar to formulation 4 (mix-legume tempeh-to-flour ratio, 60:40) (p>0.05). This study demonstrated the potential of different legume tempeh as a healthy snack product.